Love as Agape : The Early Christian Concept and Modern Discourse - Wischmeyer, Oda (Book collections on Project MUSE., 2021)
In our fraught global environment, when political and ideological lines are drawn ever sharper and old allegiances are increasingly strained, love for neighbor as both individual and societal obligation neds to be thematized and justified anew. At the same time, the New Testament call to love one's enemies forms a sharp point of contrast to the current non-culture of hatred for all things different and foreign. Oda Wischmeyer's Love as Agape: The Early Christian Concept and Modern Discourse, the ninth volume in the Baylor-Mohr Siebeck Studies in Early Christianity series, aims to bring the New Testament concept of love inot conversation with the current discussion about love. Wischmeyer investigates the commandment tradition of love for God and for neighbor, the ways in which the Septuagint and Plutarch speak of love, and the innovative concepts of love developed by Paul and John. She also presents an exegetically informed construction of the New Testament concept of love that is sharpened through a penetrating comparison with counter-, parallel, and alternative concepts from the ancient world. The book brings this holistic biblical vision forward into critical and constructive diagogue with key contemporary visions of love, including those of Julia Kristeva, Martha Nussbaum, Pope Benedict XVI, and Simon May. The tension that emerges stresses the need for fresh conceptualizations of ancient Jewish-Christian understandings, giving rise to the concluding questions of the profile, limits, and impulses of the agape concept for present challenges. Through this academically rigourous and pastorally sensitive exploration, Wischmeyer points to the great love story between God and humanity, which realizes itself in the figure of Jesus Christ. This divine romance places love as the most intense, affirming, and life-creating relationship in God's own self,, a relationship into which human beings are drawn and by which they obtain special dignity when God's love becomes their life.